Picturing Homosexual Gesture in Call me by Your Name: Gender Performativity, Sexual Identity, and Sexual Activity - Aisyah Nur Faidah; Ida Rosida (Anaphora : Journal of Language, Literary, and Cultural Studies, 2022)
The issue of LGBT is becoming one of the research fields investigated in literary studies. This topic has its critical academic discussion, especially how this behavior is related to gender, identity, gender role, and even considered destructive religious. This research aims to explore how homosexuality is depicted through homosexual gestures pictured in Call Me by Your Name, a film directed by Luca Guadagnino and released in 2017 at the Sundance film festival, United Kingdom, and the United States. This film successfully received the Best Adapted Screenplay at the 2018 Oscar. The method used is qualitative and engages with queer, Judith Butler on Gender performativity. The technique is a narrow textual analysis in which we are focused on the insight of the film's narrative text and images. We explore the homosexual gesture in Call Me by Your Name as presented by the film’s main characters, Ellio and Oliver by focusing on three performativities, namely, performance, homosexual identity, and sexual activity. The results show that in the form of homosexual gestures obtained: First, the performativity of the performance describes the general character and clothing worn by Elio and Oliver as a same-sex couple. Second, the performativity of homosexual identity shows that the actors are homosexual men. Third, the performativity of sexual activities such as kissing, and sexual deviations that are carried out in inappropriate places. In addition, the sexual relations between characters show the homoeroticism of sexual role stability, where there is a character who identifies with the sexual experience of the partner.